Nilai-Nilai Pendidikan Karakter Pada Babad Simbarjoyo - Wacana Akademika; Y. Bambang Dwiratno (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
This study aims to find and describe the values of character education contained in the Babad Simbarjoyo. The data collection technique was carried out by critically reading all the discourses and dialogues in the chronicle text. The data were analyzed by content analysis by being classified/grouped according to the theme and mandate, and the types of character education according to Komensky's theory. The output of this research is an article in the indexed national journal 'Sinta 4. The schematic of this research is TKT 1 category. The values ​​of character education in the Babad Simbar Joyo according to Komensky's model are (1) the value of virtue for the younger generation is to sacrifice for the sake of the nation and state and the loyalty of leaders in carrying out state duties, (2) the ability to distinguish good and bad in dealing with criminals so that they become self-reliant. leaders prefer good deeds for the sake of public peace, (3) Justice, is expressed when community leaders and courtiers fight robbers who violate human rights (4) Leaders are able to actualize their instincts appropriately, as the soul and attitude of a warrior who protects the people (5) Courage is expressed in self-confidence to fight the criminals who are many in number, (6) Equality of Treatment, expressed in burying the dead criminals in a way that is in accordance with the customs of the people in the village in general (7) The characters of the story Brave Taking risks, in the form of loss of life and property against criminals (8) Giving Trust to Students also needs to be imitated by Ki Hanggapati against criminals, giving confidence to his students to join the fight, (9) The story characters have the Spirit to Work Hard to crush criminals and prosper their citizens, (10) The story characters have deeds that are useful for the community. Others, namely the defense of the small people who are oppressed by criminals, (11) Instilling virtue in the characters of the story is built as early as possible so that when they grow up they are able to face problems that harm the community they lead.